Determinants of Stillbirth From Two Observational Studies Investigating Deliveries in Kano, Nigeria - Milton, Rebecca; Zara Modibbo, Fatima; Watkins, William John; Gillespie, David; Alkali, Fatima Ibrahim; Bello, Murjanatu; Edwin, Chinagozi Precious; Habib Sa ad, Fatima; Hood, Kerenza; Iregbu, Kenneth; Kassim, Aishatu; Khalid, Rashida Yakubu; et al. (Frontiers in Global Women's Health, 2022)
Background: Stillbirths are a poignant representation of global inequality. Nigeria is documented to have the second highest rate; yet the reporting system is inadequate in most Nigerian healthcare facilities. The aim was to identify determinants of stillbirth among deliveries in the Murtala Muhammad Specialist Hospital (MMSH), Kano, Nigeria. Methods: Two study designs were used: a case-control study (S1) and a prospective cohort study (S2). Both studies were carried out at the MMSH. For S1 stillbirths were retrospectively matched to a livebirth by time (target of 24 hours’ time variation) to establish a case-control study with a 1:1 ratio. Eligibility into S2 included all mothers who presented at the MMSH in labour regardless of birth outcome. Both based on recruitment durations, not sample sizes (three-months and two-months respectively 2017-2018). Demographic and clinical data were collected paper-based questionnaires. Univariable logistic regression was used. Multivariable logistic regression was used to explore relationships between area type and other specific factors. Findings: Stillbirth incidence in S2 was 180/1000 births. Stillbirth was associated with the following factors; no maternal education, previous stillbirth(s), prematurity, living in both semi-rural and rural settings and having extended time periods between rupture of membranes and delivery. Findings of the multivariable analysis (S1 and S2) indicated that the odds of stillbirth, for those living in a rural area, were further exacerbated in those mothers who had no education, lived in a shack, or had any maternal disease. Interpretation: This research identifies the gravity of this situation in this area and highlights the need for action. Further understanding of some of the findings and exploration into associations are required to inform intervention development. Funding: This collaboration was supported by funding from Health and Care Research Wales.